Cinobufagin inhibits tumor growth by inducing apoptosis through Notch signaling pathways in human cholangiocarcinoma - Ren, Jiajun; Wang, Shouhua; Jin, Longyang; Ma, Fei; Zhou, Di; Cai, Qiang (Translational Cancer Research, 2019)
Background: Many studies have shown that cinobufagin has antitumor effects against many cancers. The aim of this study was to assess the effects of cinobufagin on cholangiocarcinoma (CCA) cells. Methods: Colony formation assay, cell-counting kit-8 (CCK-8) assay, and tumor xenograft experiments were applied to investigate the function of cinobufagin on human CCA cells, in vitro and in vivo. Flow cytometric analysis was performed to validate the effects of cinobufagin on cell apoptosis. Quantitative real-time reverse transcription PCR (qRT-PCR) and Western blot assays were performed to evaluate expression levels of related genes. Results: This study found that cinobufagin inhibited proliferation in both QBC939 and RBE cells. Flow cytometric analysis indicated that rate of apoptosis was significantly increased when treated with cinobufagin. Regarding mechanism analysis, cinobufagin was found to dramatically inactivate Notch signaling pathways. Animal experiment results in vivo were consistent with outcomes in vitro. Conclusions: These data suggest that cinobufagin-mediated inactivation of Notch pathways may play an important role in the induction of apoptosis in CCA.